Polar Effects Control the Gas‐Phase Reactivity of para‐Benzyne Analogs. Issue 21 (11th September 2018) - Sheng, Huaming; Ma, Xin; Lei, Hao‐Ran; Milton, Jacob; Tang, Weijuan; Jin, Chunfen; Gao, Jinshan; Wittrig, Ashley M.; Archibold, Enada F.; Nash, John J.; Kenttämaa, Hilkka I.
Abstract: We report herein a gas‐phase reactivity study on a para‐benzyne cation and its three cyano‐substituted, isomeric derivatives performed using a dual‐linear quadrupole ion trap mass spectrometer. All four biradicals were found to undergo primary and secondary radical reactions analogous to those observed for the related monoradicals, indicating the presence of two reactive radical sites. The reactivity of all biradicals is substantially lower than that of the related monoradicals, as expected based on the singlet ground states of the biradicals. The cyano‐substituted biradicals show substantially greater reactivity than the analogous unsubstituted biradical. The greater reactivity is rationalized by the substantially greater (calculated) electron affinity of the radical sites of the cyano‐substituted biradicals, which results in stabilization of their transition states through polar effects. This finding is in contrast to the long‐standing thinking that the magnitude of the singlet‐triplet splitting controls the reactivity of para ‐benzynes. Abstract : A Gas‐phase reactivity study of a para ‐benzyne cation and its three cyano‐substituted derivatives reveals that polar effects govern their reactivities. All four biradicals were found to undergo primary and secondary radical reactions analogous to those observed for the related monoradicals, indicating the presence of two reactive radical sites.